Cinematicity in media history - Geiger, Jeffrey; Littau, Karin, 1960- (Edinburgh : Edinburgh University Press, 2013)
'This collection ... [focuses] on the relations of cinema to other media, artworks and diverse forms of entertainment, demarcating their sometimes conjoined, sometimes separate, histories ... [and] seeks to make visible the complex ways in which media anticipate, interfere with and draw on one another, demonstrating how what we have called'cinematicity' makes itself felt in practices of seeing, reading, writing and thinking both before and after the'birth' of cinema'--Page 1.
Includes bibliographical references (pages 235-239) and index.
Keywords: Motion pictures -- Social aspects; Intermediality